Factors influencing the impact of pharmacogenomic prescribing on adherence to nicotine replacement therapy: A qualitative study of participants from a randomized controlled trial. Issue 1 (29th January 2018) - Wright, Alison J; Sutton, Stephen; Armstrong, David; Aveyard, Paul; Kinmonth, Ann Louise; Marteau, Theresa M
Abstract : Among smokers trying to quit, having their nicotine replacement therapy dose tailored to genotype was not particularly remarkable and did not strongly influence medication adherence. Abstract: Pharmacogenomics may improve health outcomes in two ways: by more precise and therefore more effective prescribing, tailored to genotype, and by increasing perceived effectiveness of treatments and so motivation for adherence. Little is known about patients' experiences of, and reactions to, receiving pharmacogenomically tailored treatments. The aim of this study was to explore the impact of pharmacogenomic prescribing of nicotine replacement therapy (NRT) on smokers' initial expectations of quit success, adherence, and perceived important differences from previous quit attempts. Semi-structured interviews were conducted with 40 smokers, purposively sampled from the Personalized Extra Treatment (PET) trial (ISRCTN 14352545). Together with NRT patches, participants were prescribed doses of oral NRT based on either mu-opioid receptor (OPRM1) genotype or nicotine dependence questionnaire score (phenotype). Data were analyzed using framework analysis, comparing views of participants in the two trial arms. Although most participants understood the basis for their prescribed NRT dose, it little influenced their views. The salient features of this quit attempt were the individualized behavioral support and combined NRT, not pharmacogenomic tailoring. Participants' initial expectations of success were mostly based on prior experiences of quitting. They attributed taking medication to nurse advice to do so, and attributed reducing or stopping it to side effects, forgetfulness, or practical difficulties. Intentional nonadherence appeared very rare. Pharmacogenomic NRT prescribing was not especially remarkable to participants and did not seem to influence adherence. Where services already tailor prescriptions to phenotype and provide individualized behavioral support for treatment adherence, pharmacogenomic prescribing may have limited additional benefit.